Special issue on programming based on actors, agents and decentralized control - Ricci, Alessandro; Agha, Gul; Bordini, Rafael H.; Marron, Assaf (Science of computer programming, 2015)
The AGERE! workshop1 has been organized with the ACM SPLASH conference since 2011. The workshop has brought together researchers in programming systems, languages, and applications based on actors, active/concurrent objects, agents, and more broadly, high-level programming paradigms which facilitate decentralized control. The goal of the workshop is to promote use of such paradigms to address the problem of developing software for complex, real-world applications. The AGERE workshop is a follow on to workshops on Object-based Concurrent Programming which were organized twenty years earlier in conjunction with OOPSLA [1–3]. In the last two decades, concurrency and distribution have become part of everyday programming. In this context, the objective of AGERE! is to foster the development and adoption of high-level programming paradigms embracing concurrency at the core of the developed abstractions and constructs. This special issue collects extended and enhanced versions of selected papers from AGERE! 2011 and 2012 which underwent additional review cycles.